1997
DOI: 10.1111/j.2042-7158.1997.tb06837.x
|View full text |Cite
|
Sign up to set email alerts
|

2′,5′-Dihydroxychalcone as a Potent Chemical Mediator and Cyclooxygenase Inhibitor

Abstract: Eleven chalcone derivatives have been tested for their inhibitory effects on platelet aggregation in rabbit platelet suspension and the activation of mast cells and neutrophils. Arachidonic acid-induced platelet aggregation was potently inhibited by almost all the compounds and some also had a potent inhibitory effect on collagen-induced platelet aggregation and cyclooxygenase. Some hydroxychalcone derivatives showed strong inhibitory effects on the release of beta-glucuronidase and lysozyme, and on superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Chalcones (1-20; Table 1) were prepared by Claisen-Schmidt condensation of appropriate acetophenones with appropriate aromatic aldehyde [Lin et al, 1995;Hsieh et al, 1998] and dissolved in dimethyl sulfoxide (DMSO). Elemental analyses were within ± 0.4% of the theoretical values, unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chalcones (1-20; Table 1) were prepared by Claisen-Schmidt condensation of appropriate acetophenones with appropriate aromatic aldehyde [Lin et al, 1995;Hsieh et al, 1998] and dissolved in dimethyl sulfoxide (DMSO). Elemental analyses were within ± 0.4% of the theoretical values, unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
“…We also demonstrated that chalcones inhibited release of chemical mediators from mast cells and neutrophils [Lin et al, 1995;Hsieh et al, 1998]. …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They are the first isolable compounds from flavonoid biosynthesis in plants and have been reported to exhibit a diverse range of pharmacological activities including antiplatelet, antitumor, anti-inflammatory, antiplasmodial, immunosuppressant, and antioxidant properties [7] . For example, both natural and synthetic chalcones have been shown to exhibit antiplatelet activity [8,9] . Moreover, a series of polyphenolic chalcones have been demonstrated to activate heme oxygenase-1 in human endothelial cells and possibly can counteract oxidative stress [10] .…”
Section: Introductionmentioning
confidence: 99%
“…1) Previous studies showed that natural or synthetic chalcones with an inhibitory effect on arachidonic acid (AA)-induced platelet aggregation in washed rabbit platelets and secondary aggregation induced by epinephrine in human platelet-rich-plasma (PRP) are mainly mediated through the suppression of cyclooxygenase (COX) activity and reduced thromboxane formation or owing to inhibition of thromboxane synthase leading to the reduction of thromboxane formation. [2][3][4] In turn, we have also synthesized a series of 2′,5′-dimethoxylchalcone derivatives and reported as G 2 /M arrest-mediated apoptosis-inducing agents and inhibitors of nitric oxide production in rat macrophage. 5) During the past few years, COX (COX-1, COX-2) was discussed as new targets for several types of cancer, including breast cancer.…”
mentioning
confidence: 99%